Chemical composition and termiticidal activity of Khaya ivorensis stem bark extracts on woods - Gabriel Adetoye ADEDEJI; Olukayode Yekin OGUNSANWO; Funmilayo Sarah EGUAKUN; Taiwo Olayemi ELUFIOYE (Maderas: Ciencia y Tecnología, 2018)
The genus Khaya is extractives rich, but the extractives in the stem bark are among the most abundant, accessible and utilised materials in Nigeria. These extractives are of considerable interest for wood protection because of their pesticidal properties. In this study, the chemical constituents of Khaya ivorensis stem bark and their termiticidal activity were investigated on Triplochiton scleroxylon and Vitex doniana woods. Spectrophoto-metric and Forlin-Ciocalteu analyses showed that Khaya ivorensis stem bark contained total: alkaloids 38.98±0.02 mg/g, flavonoids 0.37±0.02 mg/g, phenol 50.62±0.11 mg/g, saponins 156.31±0.76 mg/g, and tannins 59.95±0.54 mg/g. Field tests demonstrated that the extract from Khaya ivorensis stem bark had significant termiticidal activity at tested concentrations compared to the control. The results indicated that Khaya ivorensis stem bark has potential as a natural agent for termite control.